Exploring Behavioral Dimensions of Hybrid English Learning with Eco-Context in Higher Education - Akhmad Subkhi Ramdani; Endang Iryani; Rismala Sri Hariaty; Rinto Rivanto; Deni Iskandar (SCAD Independent, 2026)
The rapid expansion of digital technology has transformed English language education and increased the adoption of hybrid learning in higher education. At the same time, universities are expected to integrate sustainability and global citizenship into their curricula. This study examines students’ attitudes and learning behaviours toward hybrid English learning that incorporates environmental and sustainability issues. Using a quantitative descriptive survey design, data were collected in 2024 from 109 undergraduate students at a university in Jakarta, Indonesia. An online questionnaire measured three constructs: attitudes toward hybrid English learning, hybrid learning behaviours, and learning behaviours in environmentally integrated English instruction. Data were analyzed using Cronbach’s alpha, Percent of Maximum Possible (POMP) scores, descriptive statistics, and Pearson correlation coefficients. The findings revealed very high attitudes toward hybrid English learning (M = 82.55), high levels of hybrid learning behaviour (M = 79.78), and high engagement in English learning integrated with environmental issues (M = 81.03). The study demonstrates that the integration of sustainability themes strengthens student engagement, technological literacy, critical awareness, and ecological responsibility. These findings suggest that hybrid English learning can serve as an interdisciplinary pedagogical model that connects language development with sustainability literacy and global citizenship in higher education.